2015
DOI: 10.1111/1348-0421.12230
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of flavaglines as potential chikungunya virus entry inhibitors

Abstract: Chikungunya virus (CHIKV) is a re-emerging mosquito-borne alphavirus that recently caused large epidemics in islands in, and countries around, the Indian Ocean. There is currently no specific drug for therapeutic treatment or for use as a prophylactic agent against infection and no commercially available vaccine. Prohibitin has been identified as a receptor protein used by chikungunya virus to enter mammalian cells. Recently, synthetic sulfonyl amidines and flavaglines (FLs), a class of naturally occurring pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…Wintachai and colleagues also suggested that the possibility of additional co factors that assist the CHIKV entry as poor infection was observed in U937 monocytic cells that also express PHB [124]. In a follow up study, Wintachai and colleagues showed that flavaglines (prohibitin ligand) was able to inhibit CHIKV entry by preventing the CHIKV and prohibitin from colocalising in HEK293T/17 cells [125,126]. These studies suggest that PHB may be the putative receptor for CHIKV.…”
Section: E2 Proteinmentioning
confidence: 99%
“…Wintachai and colleagues also suggested that the possibility of additional co factors that assist the CHIKV entry as poor infection was observed in U937 monocytic cells that also express PHB [124]. In a follow up study, Wintachai and colleagues showed that flavaglines (prohibitin ligand) was able to inhibit CHIKV entry by preventing the CHIKV and prohibitin from colocalising in HEK293T/17 cells [125,126]. These studies suggest that PHB may be the putative receptor for CHIKV.…”
Section: E2 Proteinmentioning
confidence: 99%
“…As CHIKV uses prohibitin as a receptor to entry into mammalian cells [13], Wintachai and colleagues investigated the anti-CHIKV activity of the plant-derived compounds sulfonyl amidines 1M and the flavaglines FL3 and FL23 [41], previously reported to interact with this receptor. These compounds demonstrated antiviral activity against the CHIKV strain E1:226V East-Central-South-Africa (ECSA) genotype of a Thai isolate.…”
Section: Flavaglinesmentioning
confidence: 99%
“…Prohibitin-1 was previously identified as a receptor for CHIKV entry into mammalian cells (Wintachai et al, 2012). The synthetic flavaglines sulfonyl amidine 1 m, FL3 and FL23 exert a moderate antiviral effect on CHIKV replication in HEK293T/17 cells (Wintachai et al, 2015). Two compounds (1 m and FL23) were suggested to inhibit an entry step, whereas FL3 could act at a post-entry stage.…”
Section: Flavaglinesmentioning
confidence: 99%
“…Two compounds (1 m and FL23) were suggested to inhibit an entry step, whereas FL3 could act at a post-entry stage. The co-localization of prohibitin-1 and the CHIKV E2 glycoprotein was markedly reduced in the presence of flavaglines, which may suggest an effect on receptor binding of the virus (Wintachai et al, 2015) (Table 1).…”
Section: Flavaglinesmentioning
confidence: 99%